Socio-economic Impact Evaluation of Cooperative-Based Melon Picking Agrotourism in Kebon Ayu Village - Zainab Zainab; Jalaludin (Yayasan Siti Widhatul Faeha, 2025)
Agrotourism has become a strategic approach to rural development by enhancing the socio-economic conditions of farming communities. This study evaluates the socio-economic impact of the